Influence of Spatiotemporal Difference and Input of Higher Education on Regional Economy - Li Feng (Discrete Dynamics in Nature and Society)
Scientific expenditure and distribution of higher education drive the sustainable and stable development of regional economy. Currently, China faces an imbalance in the allocation of higher education resources. To solve the problem, it is necessary to study the spatiotemporal difference of higher education development. Therefore, this paper explores how higher education varies in time and space and measures how the spatiotemporal difference and input of higher education affects regional economy. Firstly, the authors divided the influence of spatiotemporal difference and input of higher education on regional economy into four aspects. Next, the spatiotemporal differences of higher education were examined in detail. Based on the four aspects, an equilibrium model was established for regional economic development, and the law of evolution to equilibrium was analyzed. Experimental results verify the effectiveness of the established model.